ROLE OF BODYWEIGHT EXERCISE ON SKELETAL MUSCLE STRENGTH IN ELDERLY - Ramdani Hamzah; Ronny Lesmana; Renaldi Prasetia (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2021)
Aging caused such overwhelming effects on the mass of skeletal muscle. The increasing period of rest and lack of physical activity that indicate the reduced movement most likely explain much in reducing the phenotype of muscle and bone in older individuals. Sarcopenia, the age-related loss of muscle mass and strength, is the term to explain this condition. Metabolic abnormalities such as alterations in insulin sensitivity, greater deposition of fat, myosteatosis, low level of hormones, systemic inflammation, and impaired oxidative defenses caused by decreased mitochondrial activity. Accumulated evidence showed that resistance training (RT) had an abundant effect on sarcopenia, functional status, bone density, and hip fracture. Although numerous studies showed resistance training had a significant effect to improve muscular strength in the elderly. This study aims to explore the role of bodyweight exercise in improving skeletal muscle strength in the elderly. From 19 original articles, we analyzed the effects of bodyweight exercise in the population who underwent aging. Several articles were also added to explain the muscular condition in aging and its improvement after exercise. Bodyweight training has a significant role in improving skeletal muscle strength in the elderly. It induced satellite cell activity, preventing excessive proteasomal degradation, and type II motor-unit fibers proliferation which has a significant role in muscular strength.